Influence of coaches' behavior on athletes' motivation : Malaysian sport archery experience. - Abu Samah, Irza Hanie; Adekalu, Samuel Olutokunbo; Omar, Zoharah; Ismail, Ismi Arif (RS Publication, 2013)
Sports remain one of the most recognized activities that bring citizens of different nations together across the globe. In the world of sports today, the athletes’ success and failure in games tournament depends on their level of motivation which serve as an essential tool for them to achieve a set goal. This study investigates the influence of Coaches’ Behavior on Athletes’ motivation, a study on Malaysian sport archery’s experience. The study population comprises of 95 male and female archers who took part in the National Archery Circuit III competition in Sabah, Malaysia. Questionnaire was used to collect data from the study. The data collected were analyzed using frequency counts and percentages. It was found that there is a high level of motivation among athletes based on the influence of coaches’ behavior which eventually improve their performance to achieve a goal.